Deconstructing leisure time and workload: Case of women bean producers in Kenya - Nchanji, Eileen Bogweh (International Center for Tropical Agriculture, 2019)
Presented by Eileen Nchanji (International Center for Tropical Agriculture), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.